Influence of phosphorous fertilization on productivity of soybean in Kandahar, Afghanistan - Mohammad Khan Wasifhy; Obaidullah Raihan; Vijay Pooniya; Arvind Kumar; Anil Kumar Verma; Raz Mohammad Stori; Niraj Biswakarma (Annals of Agricultural Research, 2022)
A field experiment was conducted at Afghanistan National Agricultural Science and Technology University, Kandahar, Afghanistan, during April to September 2017, to determine the effects of phosphorus levels on growth, yield attributes and yields of soybean. Six phosphorus levels viz., (0, 15, 30, 45, 60 and 75 kg P2 O5 ha–1) along with local recommended doses of N and K2 O (30 and 50 kg ha–1, respectively) were applied in four replicates. Results of this experimentation indicated that, phosphorus fertilization at 75 kg P2 O5 ha–1 registered the highest number of pods plant–1 (103.1 pods), number of seeds pod–1 (3.3 seeds), seed weight plant–1 (23.3 g) and seed, straw and biological yields of soybean (2.47, 5.21 and 7.69 t ha–1, respectively). Yield attributes and yields of soybean influenced significantly by increasing phosphorus fertilization level up to 75 kg P2 O5 ha–1 in Kandahar, Afghanistan.